ANALYSIS OF ORGANIZATIONAL COMMUNICATION, TRANSFORMATIONAL LEADERSHIP STYLE ON EMPLOYEE JOB SATISFACTION WITH INTRINSIC MOTIVATION AS AN INTERVENING VARIABLE AT PT SANMAS SURABAYA - Loren Surmila Br Surbakti; Muhadjir Anwar (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Study This aim For analyze influence communication organization and style leadership transformational to satisfaction Work employee with motivation intrinsic as intervening variables at PT Sanmas Surabaya, a companies operating in the field production and distribution rice . The underlying phenomenon study This is importance effectiveness internal communication as well role inspirational leadership​ in increase satisfaction Work employees , in particular through improvement motivation sourced work​ from in self employees . Approach research used​ is quantitative with Partial Least Square – Structural Equation Modeling (PLS-SEM) technique for analyze connection intervariable . Data obtained through distribution questionnaire to 83 respondents who were employees of PT Sanmas Surabaya from various divisions. Each variables measured use indicators that have been tested validity and reliability based on study literature previous research results show that communication organization influential positive and significant to motivation intrinsic and satisfaction Work employees . Likewise , the style leadership transformational own influence positive and significant to motivation intrinsic and satisfaction work . In addition , motivation intrinsic proven play a role as intervening variables that strengthen connection between communication organization and style leadership transformational to satisfaction Work .